Kontribusi Konsep Diri terhadap Perilaku Bullying - Suci Lia Sari; Wita Antasari (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2018)
Bullying behavior was affected by nternal factors. The internal factor was self-concept. The purpose of this research was to reveal the extent to which the self-concept contributed toward bullying behavior. This research used quantitative approach and correlation method. The population of the research was the students in claas X and XI. The sample was chosen by using proportional random sampling technique. The instrument of the research was a scala of Likert model. The reliability of the instrument of the self-concept was 0.873, and bullying behavior was 0.899. the data gathered were analized by using simple regression. The research findings indicated that: 1) self-concept in general, was in average category in which physical and social aspects got the highest percentage, 2) bullying behavior in genaral was in average category in which verbal and relational bullying got the highest percentage, 2) self-concept contributed negatively and significantly toward bullying behavior.